A neural circuit encoding sexual preference in humans. (September 2016) - Poeppl, Timm B.; Langguth, Berthold; Rupprecht, Rainer; Laird, Angela R.; Eickhoff, Simon B.
Highlights: Identification of a core neural circuit using meta-analytic remodeling. Sexual preference is encoded by phylogenetically old, subcortical brain structures. Hypothalamus, thalamus, septal area, and para-/hippocampus control sexual preference. Substantia innominata regulates sexual non-preference. Abstract: Sexual preference determines mate choice for reproduction and hence guarantees conservation of species in mammals. Despite this fundamental role in human behavior, current knowledge on its target-specific neurofunctional substrate is based on lesion studies and therefore limited. We used meta-analytic remodeling of neuroimaging data from 364 human subjects with diverse sexual interests during sexual stimulation to quantify neural regions associated with sexual preference manipulations. We found that sexual preference is encoded by four phylogenetically old, subcortical brain structures. More specifically, sexual preference is controlled by the anterior and preoptic area of the hypothalamus, the anterior and mediodorsal thalamus, the septal area, and the perirhinal parahippocampus including the dentate gyrus. In contrast, sexual non-preference is regulated by the substantia innominata. We anticipate the identification of a core neural circuit for sexual preferences to be a starting point for further sophisticated investigations into the neural principles of sexual behavior and particularly of its aberrations.